The Role of Transformasional and Discipline Working on Employee Performance During Covid-19 Pandemic - Dhumas, Hiperdo; Yuliawati, (JURNAL AGRIBISAINS, 2023)
Bale Hydroponics Salatiga is an individual business unit engaged in hydroponic vegetable farming located in Bugel, Salatiga City, Central Java. The work system carried out by employees during the Covid-19 pandemic underwent changes in operational technicalities, which resulted in a decrease in income. This study aims to determine the role of transformational leadership style and work discipline on employee performance during the Covid-19 pandemic at Bale Hydroponics Salatiga. This study uses a qualitative method by observing the role of transformational leadership style and work discipline on employee performance. The technique of taking key informants and informants is done purposively. Data collection techniques were carried out by in-depth interviews with owners and employees. The data analysis technique was carried out in three stages, namely data reduction, data presentation and conclusion drawing. The validity of the data was tested by triangulation of sources and techniques. The results showed that the transformational leadership style has a role in employee performance because employees make the owner a role model in their work. The owner sets an example first at work so that it can motivate employees, roles such as making goals can be accomplished. A transformational leadership style is needed in dealing with obstacles such as the Covid-19 pandemic, so it is necessary to increase alertness and responsiveness in order to have readiness in dealing with obstacles.